THE SYSTEM OF NORMATIVE LEGAL REGULATION OF ACCOUNTING OF THE RUSSIAN FEDERATION - Z. Korzovatykh; A. Bykova (Вестник университета, 2016)
The problems of legal regulation of the accounting of financial accounting in Russia . Main attention is paid to the system of legal regulation from different points of view, found a link between the concepts of regulatory accounting, property and non-property relations . With this in mind, it presented the economic classification of accounting information users.